Brown tumor in the mandible as an initial presentation of primary hyperparathyroidism - Miranda Manrique, Gonzalo (2024)
Brown tumor (TP) is a benign bone lesion caused by excess osteoclastic activity and hemosiderin deposition as a result of primary or secondary hyperparathyroidism. We present the case of a 71-year-old male patient with a mandibular tumor and bone pain in the lower limbs. He was initially evaluated by the head and neck department who performed excision of mandibular lesion with histological result of giant cells with necrotic and hemorrhagic areas. 3 months later, hypercalcemia was evident, and he was referred to the endocrinology department. The diagnosis of primary hyperparathyroidism associated with skeletal complications was confirmed and parathyroidectomy was scheduled with histological confirmation of parathyroid adenoma. The present case is of interest because of the initial presentation of primary hyperparathyroidism associated with the presence of a brown tumor as a differential diagnosis when evaluating a patient with mandibular bone tumor.